How Re (Build) Social Capital in the (Post) COVID-19 Pandemic Era? The Raciborz Case Study - Robert Geisler; Michał Potracki (Studia z Polityki Publicznej, 2024)
The concept of social capital has been recognized as one of the key aspect of public administration and is an essential part of local urban policy. From the point of view of the inhabitants, it conveys a sense of subjectivity, achievement, participation and co-government. Much more important is that social capital will be characterized by a measurable impact in terms of civic engagement in local affairs. Racibórz was selected as a case study due to the city’s proximity to the border. On the one hand, it is regarded with a long tradition of self-government, self-organization, belonging to different legal and administrative systems throughout history, and on the other hand, with a marginal position in the territory and in the administrative structures of the country and the region. All these factors have, over the course of history, given rise to inhabitants’ behavioral patterns and created the basic forms and structures of civil society and/or social capital. Based on qualitative and ethnographic field studies, the authors presents the experiences of the COVID-19 pandemic phenomena, which changes the structures of social capital in Raciborz by reducing/destroying it and ask the question how it can be rebuilt in the future. The aim of the article is to present one of the current challenges for urban policy in Poland: social participation, especially in the context of the concept of social capital, in Raciborz town at the time of the (post) Covid-19 pandemic.